Molecular dynamics study of major urinary protein-pheromone interactions: a structural model for ligand-induced flexibility increase - Macek, Pavel; Novák, Petr; Krízová, Hana; Zídek, Lukás; Sklenár, Vladimír (FEBS letters, 2006)
Recently, two independent (15)N NMR relaxation studies indicated that in contrast to the decreased flexibility expected for induced-fit interactions, the backbone flexibility of major urinary protein isoform I (MUP-I) slightly increased upon complex formation with its natural pheromone 2-sec-butyl-4,5-dihydrothiazol. We have investigated the subtle details of molecular interactions by molecular dynamics simulations in explicit solvent. The calculated order parameters S(2) for a free- and ligand-bound protein supply evidence that mobility in various regions of MUP-I can be directly related to small conformational changes of the free- and complexed protein resulting from modifications of the hydrogen bonding network.
Keywords: molekulární modely; Protein Isoforms; feromony; terciární struktura proteinů; proteiny; vodíková vazba; Models, Molecular; Protein Structure, Tertiary; Proteins; Hydrogen Bonding; protein - isoformy; počítačová simulace; Computer Simulation; Pheromones